Prisoners with neurodevelopmental difficulties: Vulnerabilities for mental illness and self‐harm. (8th January 2020) - McCarthy, Jane; Chaplin, Eddie; Forrester, Andrew; Underwood, Lisa; Hayward, Hannah; Sabet, Jess; Young, Susan; Mills, Richard; Asherson, Philip; Murphy, Declan
Abstract: Background: Research into neurodevelopmental disorders in adult offenders has tended to be disorder specific, so hindering service planning for a group of offenders with similar vulnerabilities. Aim: To examine vulnerabilities for mental illness and self‐harming behaviours among male prisoners screening positive for a range of neurodevelopmental difficulties—including but not confined to disorders of intellectual ability, attention deficit hyperactivity, and in the autistic spectrum. Method: In a cross‐sectional study, prisoners who screened positive for neurodevelopmental difficulties were compared to prisoners who screened negative for the same on indicators of suicide‐related and self‐harm behaviours, mental illness, and substance misuse using the Mini International Neuropsychiatric Interview (MINI). Results: Of 87 prisoners who screened positive for neurodevelopmental difficulties, 69 had full MINI mental health data. In comparison with 69 neurotypical men in the same prison, the neurodevelopmental difficulties group was significantly more likely to have thought about self‐harm and suicide in the last month and to have significantly higher rates of concurrent mental disorders including psychosis, anxiety, depression, personality disorder, and substance dependency disorders. Conclusions: This is one of the first studies to examine the mental health of adults with neurodevelopmental difficulties in a prison setting. This group, unlike those who meet diagnostic threshold, is not routinely considered by mental health or correctional services. The study found prisoners with neurodevelopmental difficulties showed greater vulnerability to mental disorder and thoughts of suicide and suicide‐related behaviours than other prisoners. Accordingly, we recommend routine early screening across the criminal justice system for any neurodevelopmental difficulties to inform decision‐making on the most appropriate disposal and support.